Transplantation of Endothelial Progenitor Cells in Obese Diabetic Rats Following Myocardial Infarction: Role of Thymosin Beta-4 - Poh, Kian Keong; Lee, Poay Sian Sabrina; Djohan, Andie Hartanto; Galupo, Mary Joyce; Songco, Geronica Gorospe; Yeo, Tiong Cheng; Tan, Huay Cheem; Richards, Arthur Mark; Ye, Lei (Cells (Basel, Switzerland), 2020)
Endothelial progenitor cells (EPCs) are bone-marrow derived cells that are critical in the maintenance of endothelial wall integrity and protection of ischemic myocardium through the formation of new blood vessels (vasculogenesis) or proliferation of pre-existing vasculature (angiogenesis). Diabetes mellitus (DM) and the metabolic syndrome are commonly associated with ischemic heart disease through its pathological effects on the endothelium and consequent endothelial dysfunction. Thymosin-β4 (Tβ4) which expressed in the embryonic heart is critical in epicardial and coronary artery formation. In this study, we explored the effects of Tβ4 treatment on diabetic EPCs in vitro and intramyocardial injection of Tβ4-treated and non-Tβ4 treated EPCs following acute myocardial infarction (MI) of diabetic rats in vivo. It was found that 10 ng/mL Tβ4 increased migration, tubule formation, and angiogenic factor secretion of diabetic EPCs in vitro. In vivo, although implantation of Tβ4 treated diabetic EPCs significantly increased capillary density and attracted more c-Kit positive progenitor cells into the infarcted hearts as compared with implantation of non-Tβ4 treated diabetic EPCs, the significantly improved left ventricular ejection fraction was only found in the rats which received non-Tβ4 treated EPCs. The data suggests that a low dose Tβ4 increases diabetic EPC migration, tubule formation, and angiogenic factor secretion. However, it did not improve the effects of EPCs on left ventricular pump function in diabetic rats with MI.